The Duration of Capital Account Crises-An Empirical Analysis - Hofman, David (IMF Working Papers; Working Paper, 2007)
This paper examines the duration of capital account crises. We develop a new index to identify both the start and the end of these crises. Applying the index to a sample of 18 crisis episodes, we derive stylized facts on crisis duration and review the economic and financial circumstances that prevailed at the dusk of crises, a relatively unexplored area. We use the econometric technique of duration analysis to gauge the relative importance of various factors affecting the probability of exiting a crisis. We find that initial and external conditions are key determinants. But fiscal and monetary policies can also help shorten crisis duration.